2021
DOI: 10.5603/gp.a2021.0068
|View full text |Cite
|
Sign up to set email alerts
|

Different modes of delivery and hormonal stress response

Abstract: This article is available in open access under Creative Common Attribution-Non-Commercial-No Derivatives 4.0 International (CC BY-NC-ND 4.0) license, allowing to download articles and share them with others as long as they credit the authors and the publisher, but without permission to change them in any way or use them commercially.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Notably, numerous of the included studies did not report on delivery mode and time of delivery even though labour and diurnal variations can affect the umbilical cortisol levels (Bublitz et al, 2018; Bulska et al, 2021; Kiriakopoulos et al, 2019; Mears et al, 2004; Sano et al, 2015) and perhaps also the placental activity of HSD11β2 (Huebner et al, 2021). This is underlined by the study of Lamade et al (Lamadé et al, 2021) that found the activity of HSD11β2 correlated with the time of day of the amniocentesis procedure with a peak in the enzyme activity in the morning (Bublitz et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, numerous of the included studies did not report on delivery mode and time of delivery even though labour and diurnal variations can affect the umbilical cortisol levels (Bublitz et al, 2018; Bulska et al, 2021; Kiriakopoulos et al, 2019; Mears et al, 2004; Sano et al, 2015) and perhaps also the placental activity of HSD11β2 (Huebner et al, 2021). This is underlined by the study of Lamade et al (Lamadé et al, 2021) that found the activity of HSD11β2 correlated with the time of day of the amniocentesis procedure with a peak in the enzyme activity in the morning (Bublitz et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Cortisol and prolactin (PRL): the maternal cortisol and prolactin in serum were determined by competitive ELISA kits, DiaMetra ELISA 28 and EIA kit respectively. 29 …”
Section: Methodsmentioning
confidence: 99%
“…The concentration was determined as per the manufacturer's protocol and by measuring the end-point colour intensity using a spectrophotometer at 450 nm. 26 Cortisol and prolactin (PRL): the maternal cortisol and prolactin in serum were determined by competitive ELISA kits, DiaMetra ELISA 28 and EIA kit respectively. 29…”
Section: Quantification Of Serum Hormonesmentioning
confidence: 99%
“…During pregnancy and delivery, stressful situations are correlated with an elevation in the PRL and cortisol secretion. Exposure to stress in the early prenatal period may impact the individual phases of neonatal development [3]. On the other hand, IGF-2 is an essential growth factor regulating growth, especially during the normal physiological fetal development [4].…”
Section: Introductionmentioning
confidence: 99%